A Review of Pediatric Cardiovascular Risk Factors and Current Guidelines - Sarma, Deeksha; Benedict, Lawrence M.; Moulick, Achintya; Stevens, Randy; Mahan, Vicki (Scientific Research, 2018)
Dyslipidemia is a highly prevalent condition, and includes a collection of diseases that cause increased levels of plasma triglycerides and/or cholestrol, or decreased levels of HDL-C, with a prototypical disease being familial hypercholesterolemia. Dyslipidemic conditions promote increased atherogenesis through the oxidation of lipids by macrophages, and an increased response to injury by the vascular endothelium. This vascular damage, loss of vascular compliance, and overall hardening of arteries lead to sequellae such as cardiovascular disease, cerebrovascular events, and aneurysm formation. It has been established that certain risk factors predispose individuals to the sequellae of atherosclerosis, including smoking, diabetes, hypertension, and hyperlipidemia. However, studies show that these risk factors can be seen in children as well. This review aims to assess the effect of these risk factors and demonstrate their effects through adolescence into adulthood
Keywords: Cardiovascular Disease; Familial Hypercholesterolemia; Dyslipidemia; Atherosclerosis